Starejši hidrotehniki, ki so delovali na širšem slovenskem prostoru - Krajnc, Uroš (Gradbeni vestnik, 2023)
The article deals with older hydraulic engineers who worked in the wider Slovenian area between the 15th and 19th centuries. As the Slovenian territory at that time belonged to the states of Austria and Venice, the experts were representatives of all the peoples living in Austria and Venice. The article presents hydraulic engineers in the broadest sense, all those who researched, designed and carried out interventions in water. Many are not known to have even worked on Slovenian territory at all (Leonardo da Vinci), some were successful not only in hydrotechnics but also in politics (Gabrijel Gruber), others were top experts in science (Jožef Mrak, Jurij Vega, Balthasar Hacquet) or accurately described all Slovenian waters (Valvazor).
Keywords: 15.–19. stoletje; 15th–19th century; Baltazar Hacquet; Gabrijel Gruber; hidrotehniki; hydrotechnicians; Jožef Mrak; Jurij Vega; Leonardo da Vinci; širše slovensko ozemlje; wider Slovenian territory